2008
DOI: 10.1590/s0100-40422008000100002
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento e validação de método de análise de glifosato em grãos de soja

Abstract: Recebido em 6/6/06; aceito em 14/6/07; publicado na web em 3/12/07 DEVELOPMENT AND VALIDATION OF A METHOD OF ANALYSIS OF GLYPHOSATE IN SOY GRAINS. The main objective of this work is to develop an efficient procedure to determine glyphosate in soybean grains. The cleanup of the aqueous extracts was done in two steps, beginning with liquid-liquid partitioning and then solid-phase extraction with anion exchange resin. After derivatization with a mixture of trifluoroacetic anhydride (TFAA) and trifluoroethanol (TF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 9 publications
0
11
0
2
Order By: Relevance
“…and makes the plants resistant to the action of glyphosate (ABREU; MATTA; MONTAGNER, 2008). According to Lima et al (2011) the technology that has provided the greatest impact on weed management in the last 10 years has been the introduction of varieties which are resistant to herbicides.…”
Section: Introductionmentioning
confidence: 99%
“…and makes the plants resistant to the action of glyphosate (ABREU; MATTA; MONTAGNER, 2008). According to Lima et al (2011) the technology that has provided the greatest impact on weed management in the last 10 years has been the introduction of varieties which are resistant to herbicides.…”
Section: Introductionmentioning
confidence: 99%
“…Malatesta et al [31] observed, by ultrastructural analysis and immunocytochemistry, changes in the pancreas, testicules and liver of rats subjected to RR soy intake and there is a possibility that such effects related to the accumulation of herbicide present in the resistant soybean [32]. This demonstrates a possible health risk that uninformed CF users may be vulnerable.…”
Section: Resultsmentioning
confidence: 99%
“…Ao final do experimento foi determinada a concentração de glyphosate e seu metabólito AMPA na solução hidropônica, segundo método descrito por Abreu et al (2008), empregando GC-MS. O ensaio foi realizado sob o delineamento inteiramente casualizado com três repetições, com as médias comparadas pelo teste t de Student a 5% de probabilidade.…”
Section: Methodsunclassified